2006
DOI: 10.1021/jo061095b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Fluoroazetidines

Abstract: N-(Alkylidene or 1-arylmethylidene)-2-propenylamines were regiospecifically functionalized to novel N-(alkylidene or 1-arylmethylidene)-3-bromo-2-fluoropropylamines, which were proven to be excellent precursors for 3-fluoroazetidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…12 The resulting bromofluorinated imines can be used to synthesize the corresponding 3-fluoroazetidines, as described above. 9,10 At first, it was tried to extend this strategy toward the synthesis of 3-alkyl-3-fluoropyrrolidines, using N-(diphenylmethylidene)-3-methyl-3-butenylamine 5 as starting material for the bromofluorination reaction (Scheme 1). The latter imine 5 was obtained via a 4-step reaction sequence starting from commercially available 3-methyl-3-buten-1-ol 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The resulting bromofluorinated imines can be used to synthesize the corresponding 3-fluoroazetidines, as described above. 9,10 At first, it was tried to extend this strategy toward the synthesis of 3-alkyl-3-fluoropyrrolidines, using N-(diphenylmethylidene)-3-methyl-3-butenylamine 5 as starting material for the bromofluorination reaction (Scheme 1). The latter imine 5 was obtained via a 4-step reaction sequence starting from commercially available 3-methyl-3-buten-1-ol 1.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent reduction of the carbonyl function then led to the desired 3-fluoropyrrolidines. 8 Earlier research at our department demonstrated the use of N-(alkylidene or 1-arylmethylidene)-2-propenylamines 9 and N-(diphenylmethylidene)-2-propenylamines 10 as suitable precursors for the synthesis of new 3-alkyl-and 3-aryl-3-fluoroazetidines. A regioselective bromofluorination of the carbon-carbon double bond of N-alkenylimines afforded the corresponding bromofluorinated N-alkylimines, which were subsequently treated with reducing agents to obtain the corresponding amines, yielding the desired 3-fluoroazetidines after cyclization via intramolecular substitution of the bromine atom.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 3‐substituted azetidines from properly decorated 3‐halo‐ or 3‐sulfonyloxyazetidines has been covered in 2009, although without a systematic analysis to elucidate the influencing parameters on these transformations and the intervention of transient 1‐azoniabicyclo[1.1.0]butane cations …”
Section: Preparation and Synthetic Utilization Of Bicyclic Aziridinimentioning
confidence: 99%
“…For instance, initial conversion of alkenes to vic-diols, e.g. via epoxidation, can be followed by C-C bond cleavage with NaIO 4 or HIO 4 , with often high selectivity and typically full conversion (Scheme 1), [12,13] which outweighs the "single step" benefit of direct treatment of alkenes with ozone, Cr 2 O 7 2- [14] or MnO 4 -. [15,16] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%